Monetary stability in Europe - Collignon, Stefan, 1951- (Routledge international studies in money and banking, 2002)
In this book, the author presents fresh perspectives on the theories surrounding European Monetary Union. Urging the reader to examine conventional ideas from new viewpoints, he discusses the events which led to EMU, analyses the current situation, and projects possible futures. Essential reading for academics and professionals concerned with the background and implications of EMU, this book will also be of considerable interest to scholars in the fields of European studies, monetary economics, international economics and economic history.